Innovative Strategies to Improve Learning Outcomes and Character Development in Elementary Students - Agnesta Putri, Lara; Januar, Exsaris; Fuja, Siti (Sekolah Tinggi Agama Islam Solok Nan Indah, 2024)
Islamic Education plays a crucial role in shaping students' religious and moral character from an early age. However, the implementation and learning outcomes of Islamic Education at the elementary school level often fall short of expectations in terms of academic achievement and the application of religious values in daily life. This study aims to analyze the influence of teaching strategies on learning outcomes in Islamic education. A qualitative approach with a case study design was employed. The study participants consisted of fourth-grade students selected through purposive sampling based on criteria relevant to the research focus. Data were collected through in-depth interviews and analyzed thematically using NVivo 10 software. The findings reveal that student-centered learning strategies significantly contribute to improving learning outcomes. The Student Team Achievement Division strategy, which engages students in heterogeneous group learning, fostered collaboration, interaction, and deeper conceptual understanding. This strategy also accommodates diverse learning styles, including visual, auditory, and kinesthetic preferences. These findings offer critical insights into developing innovative teaching strategies to enhance the quality of Islamic Education instruction. Furthermore, this study provides a foundation for future research in different contexts to enrich value-based and collaborative learning approaches.